2017
DOI: 10.5424/sjar/2017152-10753
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation pattern and acidification potential of different sources of carbohydrates for ruminants given high concentrate diets

Abstract: The in vitro fermentation pattern of five sources of carbohydrates of differing nature (maize grain, MZ; sucrose, SU; wheat bran, WB; sugarbeet pulp, BP; and citrus pulp, CT) under conditions of high concentrate diets for ruminants was studied. A first 8 h incubation trial was performed under optimal pH using inoculum from ewes given a fibrous diet, to compare fermentative characteristics of substrates. As planned, incubation pH ranged within 6.3 to 6.6. The gas produced from CT was higher than MZ, SU and BP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…In agreement with previous in vitro [ 14 , 21 ] and in vivo [ 10 , 20 , 23 ] studies, the total VFA daily production was unaffected by the inclusion of DCP in the diet, but the VFA profile was markedly affected. Studies investigating the influence of DCP on the rumen VFA profile have produced contrasting results, but some of them reported shifts to greater acetate and lower propionate proportions, resulting in greater acetate/propionate ratios [ 10 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous in vitro [ 14 , 21 ] and in vivo [ 10 , 20 , 23 ] studies, the total VFA daily production was unaffected by the inclusion of DCP in the diet, but the VFA profile was markedly affected. Studies investigating the influence of DCP on the rumen VFA profile have produced contrasting results, but some of them reported shifts to greater acetate and lower propionate proportions, resulting in greater acetate/propionate ratios [ 10 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Due to the great content of highly-degradable NDF and readily fermentable carbohydrates, DCP has a high nutritional value and it has been proposed as a possible substitute of cereals in ruminant diets [ 10 , 11 ]. Several in vitro [ 12 , 13 , 14 ] and in vivo [ 15 , 16 , 17 ] studies evaluated the inclusion of DCP in the diet of small ruminants, mainly in sheep. These studies showed that replacing barley or other cereals by DCP can increase rumen pH [ 18 , 19 ], fiber digestibility [ 15 , 20 ], and acetate proportion [ 10 , 21 , 22 ], with no effects on either total volatile fatty acid (VFA) production [ 10 , 21 ] or microbial protein synthesis (MPS) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high concentration of lactic acid with CP at 6 h ( Table 2), it did not achieve the range considered as a risk of acidosis in vivo [30] and, in fact, did not promote the values of incubation pH below 5.5 that are considered as a threshold for the onset of subacute acidosis [49]. These results were in agreement with those found by Amanzougarene et al [42] in a batch culture with a minimum buffer concentration, and could be associated with its richness in soluble sugars [50,51], estimated as 0.24 g/kg DM (Table 1), which are fermented at a very fast rate. Although CP also has a high proportion of soluble fibre (0.42, Table 1), this response cannot be directly associated with the fast fermentation of pectin [37,52], since BP includes a similar NDSF proportion (0.46) and it was fermented at a slower rate and magnitude.…”
Section: Effect Of Different Substrates On the In Vitro Fermentation supporting
confidence: 91%
“…This parameter was especially low compared to the extent of the rumen degradation of starch-rich sources (around 0.70-0.80 [40]) or fibrous sources (ranging from 0.40 to 0.70 [41]). This is difficult to explain, but we have also observed this low response in previous in vitro experiments [42], partly associated with a low pH [13]. Calsamiglia et al [43] justified similar results by the differences between rumen and in vitro microbial ecosystems, partly because the dilution of inoculum in the latter reduces the extent of the degradation.…”
Section: Effect Of the Inoculum Source On The In Vitro Fermentation Psupporting
confidence: 70%
“…The adjustment of the buffering capacity of the medium to fit the incubation pH has also been applied to the study of the acidification potential of cereal grains and carbohydrates of different characteristics [ 26 , 49 ], by allowing to ferment substrates in a low buffered medium (calculated for adjusting to pH 5.50). In these studies, the incubation period was shortened to 10 h to avoid biased results in the fermentation profile because of extreme low pH (around pH 5.0 or below) after buffer exhaustion.…”
Section: Adapting the In Vitro Model To High Concentrate Feeding Cmentioning
confidence: 99%